2016
DOI: 10.1242/dev.133165
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila astrocytes cover specific territories of CNS neuropil and are instructed to differentiate by Prospero, a key effector of Notch

Abstract: Astrocytes are crucial in the formation, fine-tuning, function and plasticity of neural circuits in the central nervous system. However, important questions remain about the mechanisms instructing astrocyte cell fate. We have studied astrogenesis in the ventral nerve cord of Drosophila larvae, where astrocytes exhibit remarkable morphological and molecular similarities to those in mammals. We reveal the births of larval astrocytes from a multipotent glial lineage, their allocation to reproducible positions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(170 citation statements)
references
References 61 publications
10
158
1
1
Order By: Relevance
“…In order to characterize the cellular organization of the NG in the adult VNC, we expressed fluorescent reporters under the control of two Gal4 drivers, alrm-Gal4 (astrocyte specific; Doherty et al, 2009) and R56FO3-Gal4 (EG specific; Kremer et al, 2017; Peco et al, 2016; Pfeiffer et al, 2008), which we confirmed are expressed in all adult astrocytes and EG, respectively (Figures 1 and S1). We also used as a marker Distalless (Dll), which we found to be expressed in all NG in the adult VNC (Figure S1).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In order to characterize the cellular organization of the NG in the adult VNC, we expressed fluorescent reporters under the control of two Gal4 drivers, alrm-Gal4 (astrocyte specific; Doherty et al, 2009) and R56FO3-Gal4 (EG specific; Kremer et al, 2017; Peco et al, 2016; Pfeiffer et al, 2008), which we confirmed are expressed in all adult astrocytes and EG, respectively (Figures 1 and S1). We also used as a marker Distalless (Dll), which we found to be expressed in all NG in the adult VNC (Figure S1).…”
Section: Resultsmentioning
confidence: 69%
“…In a second experiment, we used Dll-Gal4 to activate the Flybow system ( UAS-FB1.1 ), which permanently labels cells with different fluorescent markers (Hadjieconomou et al, 2011). We co-stained the resulting adult VNCs with Prospero, which is expressed in astrocytes but not in EG (Griffiths and Hidalgo, 2004; Peco et al, 2016) (Figures 2F and S1). Based on Prospero expression and morphology, we found that both astrocytes and EG were labeled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subset of Drosophila glial cells examined in this study has been named 'interface glia' (Ito et al, 1995), 'longitudinal glia' (Beckervordersandforth et al, 2008), 'astrocyte-like glia' (Awasaki et al, 2008), and, most recently, just 'astrocytes' Muthukumar et al, 2014;Peco et al, 2016), based on their morphology and molecular identity. The present study is the first to characterize the electrical membrane properties of Drosophila astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity of Eaat1 antiserum was confirmed by loss of Eaat1 immunoreactivity in Eaat1 null mutants. (Peco et al, 2016).…”
Section: Antibody Characterizationmentioning
confidence: 99%